Evaluation of a spherical video-based virtual reality intervention designed to teach adaptive skills for adults with autism: a preliminary report. Issue 3 (3rd April 2021) - Schmidt, Matthew; Schmidt, Carla; Glaser, Noah; Beck, Dennis; Lim, Mark; Palmer, Heath
ABSTRACT: Information and communication technologies (ICT) have been widely adopted in the intervention literature for individuals with Autism Spectrum Disorder (ASD). The systematic and predictable nature of ICTs make them particularly attractive for individuals with ASD. One ICT that has potential promise for individuals with ASD is virtual reality (VR). However, to date there is limited evidence of intervention effects for individuals with ASD when delivered via VR. The aim of this study was to extend the literature on the use of VR with individuals with ASD by presenting the design, implementation, and formative evaluation of a spherical video-based virtual reality (SVVR) mobile app. Using Design Based Research methods, we conducted a formative evaluation to investigate the SVVR app from the perspectives of (1) user experience, (2) feasibility, (3) relevance, and (4) usability for adults with ASD. The evaluation was conducted in two phases and consisted of expert review with four content experts and structured usage testing with five adults with ASD. Results indicate that participants with ASD found the SVVR app to be easy to use and reported an overall positive user-experience; results from expert review suggest a feasible, relevant, and easy-to-use intervention. The pedagogical and theoretical footing that informed the design and implementation of the SVVR mobile app for individuals with ASD is presented and discussed.